Burden of asthma, dyspnea, and chronic cough in South Asia - Bishwajit, Ghose (Int J Chron Obstruct Pulmon Dis, 2017)
BACKGROUND: Asthma, dyspnea, and chronic cough are well-established risk factors of COPD and often associated with exacerbation of the disease, which is a leading cause of morbidity and mortality in South Asian countries. OBJECTIVE: The aims of this study were to, 1) measure the prevalence of asthma, dyspnea, and chronic cough, and 2) assess the relationship between these respiratory problems and self-reported health status among South Asians. METHODS: Data for this research came from the World Health Survey (2002–2003) conducted by the World Health Organization. Subjects were 35,929 men and women, aged 18 years and older, selected from Bangladesh, India, Nepal, Pakistan, and Sri Lanka. Crude prevalence rates of asthma, dyspnea, and chronic cough were presented as percentages, and the results of their association with subjective health status were presented as odds ratios and corresponding 95% CIs. RESULTS: Prevalence of daily smoking was highest in Bangladesh (39.9%) and lowest in Sri Lanka (14.1%). Prevalence of asthma was highest in India (6.3%), while Nepal had the highest prevalence of dyspnea (11.3%) and chronic cough (15.3%). Overall prevalence of asthma and dyspnea was higher among women, while that of chronic cough was higher among men. Significant differences were observed in the prevalence rates of all the conditions among regular, occasional, and nonsmokers. A majority of the men and women who had asthma, dyspnea, and chronic cough had higher likelihood of reporting poor health status compared to those who did not have these diseases. CONCLUSION: Findings suggest that prevalence rates of asthma, dyspnea, and chronic cough were considerably high in all the countries and were significantly associated with poor subjective health. Being a high COPD-prone region, programs targeted to address these diseases could help reduce the burden of COPD and respiratory disease-related mortalities in South Asia.